Closure disclosure—mine closure planning and reporting through an ESG lens - Finucane, SJ; Bibby, RA (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
ESG (Environment, Social, Governance) is fundamentally a tool to measure business risk and opportunity. Companies that understand how ESG factors can impact or influence their business are generally more attractive to those that want to invest in an ethical manner than companies that do not have this insight. Most mining companies with shareholders and investors routinely consider and report on ESG factors in relation to mining operations, but it is not as common to consider mine closure through an ESG lens. The term ‘ESG’ relates to a framework of indicators that can be used to measure the sustainability and ethical impact of a company or investment as a way of mitigating business risks and identifying new business opportunities. Mining companies are progressively seeking alignment with key ESG values, and investors are increasingly prioritising ESG in their investment appraisals. However, investors can only reward solid ESG performance if they can access the right information to inform due diligence assessments and investment decisions. Investors usually refer to corporate sustainability reports during such assessments, but these often contain only data on rehabilitation footprints. By comparison, many ESG disclosure frameworks require mine closure information, but many mining companies do not consider mine closure risks as material and therefore do not include this the information in their disclosures and associated reporting. This paper discusses how selected sustainability and ESG disclosure frameworks address mine closure. These comprise the Global Reporting Initiative’s Sustainability Reporting Standards, the Sustainability Accounting Standards Board’s Sustainability Standards, the Task Force on Climate-related Financial Disclosures, the Carbon Disclosure Project and the International Council on Mining and Metals’ Sustainable Development Framework, along with the recently adopted Post-2020 Global Biodiversity Framework. The way in which 12 mining and mineral processing companies have addressed mine closure under these frameworks in their sustainability and ESG reports is also discussed, along with observations on mine closure planning, implementation and reporting through an ESG lens including promotion of closure credentials when reporting to investor-recognised frameworks.
Keywords: ESG; sustainability reporting; mine closure; disclosure frameworks; climate-related financial disclosures; biodiversity; nature-positive